2008
DOI: 10.1038/sj.bjc.6604477
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitisation by manganese superoxide dismutase inhibition is caspase-9 dependent and involves extracellular signal-regulated kinase 1/2

Abstract: Chemoresistance and therapeutic selectivity are major obstacles to successful chemotherapy of ovarian cancer. Manganese superoxide disumutase (MnSOD) is an important antioxidant enzyme responsible for the elimination of superoxide radicals. We reported here that MnSOD was significantly elevated in ovarian cancer cells and its overexpression was one of the mechanisms that increased resistance to apoptosis in cancer cells. Knockdown of MnSOD by small-interfering RNA (siRNA) led to an increase in superoxide gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
(46 reference statements)
3
21
0
Order By: Relevance
“…Although enhanced ROS generation is associated with inhibition of mitochondrial respiration and apoptosis, SODs can be involved in protecting the cell from oxidative injury and survival (10,40,107,126). Consistent with these results, several studies have reported the chemoresistant potential of MnSOD expression and activity (16,41,53,103,134,154). Thus, the presence of SODs can decrease the efficacy of anticancer drugs with a ROS-dependent mechanism of action, such as mofarotene, adriamycin and mitomycin C (13,50,53).…”
Section: Mitochondrial Involvement In Cancersupporting
confidence: 68%
“…Although enhanced ROS generation is associated with inhibition of mitochondrial respiration and apoptosis, SODs can be involved in protecting the cell from oxidative injury and survival (10,40,107,126). Consistent with these results, several studies have reported the chemoresistant potential of MnSOD expression and activity (16,41,53,103,134,154). Thus, the presence of SODs can decrease the efficacy of anticancer drugs with a ROS-dependent mechanism of action, such as mofarotene, adriamycin and mitomycin C (13,50,53).…”
Section: Mitochondrial Involvement In Cancersupporting
confidence: 68%
“…10 Several other studies showed that high expression of MnSOD in some cancer cells were correlated with resistance to the treatment, metastasis, and poor prognosis. [4][5][6][7][8][9]15 Reddy et al 16 identified several genes that regulate the degree of malignancy in glioblastoma multiforme. One of them is MnSOD that increased in most of primary GBM.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Moreover, MnSOD has been observed as an anti-apoptotic molecule, and increasing of MnSOD in tumor could lead to treatment resistance and tumor metastatasis. [7][8][9] Our previous study using glioma tissues from glioma patients showed that the expression of MnSOD mRNA was higher in high grade glioma than in low grade glioma and it was associated with the increase of oxidative defects. Moreover, our research proved that the expression of MnSOD mRNA was correlated with the tumor grade.…”
mentioning
confidence: 99%
“…Experimental studies have shown that Mn-SOD overexpression elevated the expression levels of several transcription factors including c-fos, c-jun, and c-Myc, resulting in expression of many growth-promoting genes in human cells (Guo et al 2003;Wenk et al 1999). Enhanced Mn-SOD expression is also protective and promotes cell survival against anticancer drugs and ionizing radiation by scavenging oxygen radicals in various human cancers including OSCC (Fisher and Goswami 2008;Kalen et al 2006;Yeung et al 2008). In addition, high expression levels of Mn-SOD have been observed in a wide range of human malignancies, including lung (Chung-man Ho et al 2001), esophageal (Janssen et al 2000), colorectal (Janssen et al 1998), and brain cancers (Landriscina et al 1996;Ria et al 2001), and are associated frequently with metastasis and poor patient prognosis.…”
Section: Discussionmentioning
confidence: 97%